Elbow terrible triad: Advancing current concepts in the treatment of 13 cases - Edgar Barros Prieto; Eduardo Noboa; Carlos Ballesteros; Carlos Peñaherrera; Francisco Endara; Alejandro Barros Castro (Trauma Case Reports)
Background: The “terrible triad” of the elbow is characterized by a combination of elbow dislocation with fractures of the radial head and the coronoid process of the ulna. This injury is notoriously complex due to the rupture of key elements that ensure elbow stability, resulting in poorer outcomes compared to simpler joint injuries. Despite advances in treatment protocols, an optimal surgical approach and fixation technique standard have not yet been established. Methods: This descriptive study focused on reviewing the anatomical and clinical characteristics of the elbow joint, considering the most current biomechanical concepts. Management protocols implemented in our practice were evaluated, including specific surgical techniques and fixation methods based on a deep understanding of elbow anatomy and biomechanics. Retrospective data were collected from patients treated at our centers, analyzing postoperative clinical and radiographic outcomes. Results: The implementation of a treatment based on updated concepts of elbow biomechanics and anatomy showed a significant improvement in postoperative joint stability and functional recovery of patients. There was a reduction in complication rates and an improvement in clinical outcomes compared to traditional approaches. The selection of specific fixation techniques and surgical approaches allowed for more effective management of the “terrible triad,” adapting to the particularities of each case and optimizing results. Conclusion: This study highlights the importance of a detailed understanding of elbow biomechanics and anatomy for the effective management of the “terrible triad.” The implementation of protocols based on these principles can significantly improve clinical outcomes and reduce complications, offering a comprehensive approach to addressing this complex pathology.Level of Evidence: IV